2016
DOI: 10.1002/2015jg003195
|View full text |Cite
|
Sign up to set email alerts
|

Near‐neutral carbon dioxide balance at a seminatural, temperate bog ecosystem

Abstract: The majority of peatlands in the temperate zone is subjected to drainage and agricultural land use and have been found to be anthropogenic emission hot spots for greenhouse gases. At the same time, many peatlands receive increased atmospheric nitrogen (N) deposition by intensive agricultural practices. Here we provide eddy covariance measurements determining net ecosystem carbon dioxide (CO2) exchange at a protected but moderately drained ombrotrophic bog in Northwestern Germany over three consecutive years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 90 publications
(128 reference statements)
1
23
0
Order By: Relevance
“…At the SPRUCE study site, using a unique collar enclosure method (1.13 m 2 ) that excluded trees (but likely not tree roots) Hanson et al [] reported annual NEE ranging from a slight sink of −3.1 g C m −2 yr −1 in 2013 to a C source ranging from 21 to 65 g C m −2 yr −1 across 2011, 2012, and 2014 (our main year of measurement). Annual net CO 2 exchange for temperate bogs typically ranges from slight sources (10 g C m −2 yr −1 ) to slight sinks (−76 g C m −2 yr −1 ) depending on bog site and the variable environmental conditions including water table, snow cover, and day and nighttime temperatures [ Lafleur et al ., ; Sottocornola and Kiely , ; Hommeltenberg et al ., ; Hurkuck et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…At the SPRUCE study site, using a unique collar enclosure method (1.13 m 2 ) that excluded trees (but likely not tree roots) Hanson et al [] reported annual NEE ranging from a slight sink of −3.1 g C m −2 yr −1 in 2013 to a C source ranging from 21 to 65 g C m −2 yr −1 across 2011, 2012, and 2014 (our main year of measurement). Annual net CO 2 exchange for temperate bogs typically ranges from slight sources (10 g C m −2 yr −1 ) to slight sinks (−76 g C m −2 yr −1 ) depending on bog site and the variable environmental conditions including water table, snow cover, and day and nighttime temperatures [ Lafleur et al ., ; Sottocornola and Kiely , ; Hommeltenberg et al ., ; Hurkuck et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning sites analyzed in our study, Aurela et al (2007) reported that at the nutrient-poor fen FI-Sii site, drought increased respiration and thus diminished carbon uptake; Adkinson et al (2011) reported that reduced water availability constrained photosynthesis capacity at the rich fen CAWp3 and consequently suppressed NEE, while the poor fen CA-Wp2 did not show a significant response to the lower water table. At the moderately rich treed fen CA-Wp1 site, Flanagan and Syed (2011) reported that both photosynthesis and respiration increased in response to the warmer and drier conditions; Hurkuck et al (2016) stated that temperature and light played a more important role than water table depth in controlling respiration and photosynthesis at the DE-Bou bog. Based on the field observations, the timing, duration, and intensity of drought have a major impact on the responses of peatland ecosystems.…”
Section: Orchidee-peat Groups Various Peatland Vegetation Into One Plmentioning
confidence: 99%
“…micrometeorological (Mauder and Foken, 2004) (Hurkuck et al, 2016) which was placed next to the ΣN r setup allows us to calculate correction factors after IPS for ΣN r .…”
Section: In-situ Power-spectral Methods [Ips]mentioning
confidence: 99%
“…It is an ombrotrophic, moderately drained bog with high ambient NH 3 concentrations (Zöll et al, 2016) dominating the local deposition of ΣN r (Hurkuck et al, 2014). A detailed description of the site is given in Hurkuck et al (2014Hurkuck et al ( , 2016).…”
Section: Sites and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation